Keefektifan “Proses Guru” Sebagai Teknik Bimbingan Kelompok untuk Meningkatkan Kemampuan Pengambilan Keputusan Karier Siswa SMK - Hanggara, Guruh Sukma (Jurnal Kajian Bimbingan dan Konseling, 2016)
Career decision-making abilities are an important part of a student's career development continuum. This research aims to determine the effectiveness of the GURU (Ground, Understand, Revise, Use) process as a group guidance technique to improve vocational school students' career decision-making abilities. The Pretest-Posttest Control Group Design experimental method was used in this research and the subjects were 12 students of SMKN 1 Trenggalek. Data analysis using the Two Independent Sample Test Mann Whitney U, obtained the Asymp value. Sig. (2-tailed) of 0.03 < real level ( /2 = 0.05) and it was concluded that the "GURU Process" as a group guidance technique was effective in improving the career decision making abilities of vocational school students. From these results, the researcher suggests that Counselors/BK Teachers can collaborate the TEACHER process with various other approaches, using it to develop various student potentials by paying attention to their development stages, psychological aspects and intervention content. Future researchers are advised to examine the GURU process with other research designs such as Single-Subject Designs or action research and pay attention to the use and feasibility of the instrument and its validity, as well as applying it to develop various other psychological aspects such as motivation, self-esteem, self-efficacy, critical thinking skills, the ability to think respectfully and so on.